Reviews. Issue 3 (1st September 2017) - Young, Elizabeth Drummond; Stafford, Patrick; Kuchler, Karin; Mackiewicz, Alison
The Gift of the Other: Levinas, Derrida and a Theology of Hospitality, Andrew Shepherd (2014) Eugene, OR: Pickwick Publications, xi + 264 pp., ISBN: 9781620327661, p/bk, 30.00Prison Food in America, Erika Camplin (2017) Lanham: Rowman and Littlefield, vii + 137 pp., ISBN: 9781442253476, h/bk, 38.00Europe after Derrida: Crisis and Potentiality, Agnes Czajka and Bora Isyar (eds) (2014) Edinburgh: Edinburgh University Press, xi + 170 pp., ISBN: 9780748683369, h/bk, £65.00Drinking Dilemmas: Space, Culture, Identity, Thomas Thurnell-Read (ed.) (2016) Abingdon: Routledge, xv + 220 pp., ISBN: 9781138931145, h/bk, £90.00